2015
DOI: 10.1590/1678-7328
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of histopathology and immunohistochemistry of indefinite round cell cutaneous tumors and characterization of canine lymphoma

Abstract: With the purpose of shedding light on some doubts in veterinary oncology, the present article intends to compare the results of histopathological and immunohistochemical examinations of unspecific round cell neoplasia, to realize immunophenotyping of canine lymphoma cases, to establish the T or B origin of neoplastic cells, and to determine the degree of proliferation and apoptosis of lymphomas by immunohistochemistry. Of 11 animals presenting immunohistochemical diagnosis of lymphoma, five had been diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
(21 reference statements)
1
4
0
3
Order By: Relevance
“…CTCL rarely metastasize (Moore et al, 1994;Yoon et al, 2014); however, when metastasis does occur, is usually restricted to a single organ (Moore et al, 1994). However, Fictum et al (2009), and more recently, Yoon et al (2014) described multisystemic metastasis of CTCL in dogs, both characterized by CD3+ neoplastic cells, as described in our study.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…CTCL rarely metastasize (Moore et al, 1994;Yoon et al, 2014); however, when metastasis does occur, is usually restricted to a single organ (Moore et al, 1994). However, Fictum et al (2009), and more recently, Yoon et al (2014) described multisystemic metastasis of CTCL in dogs, both characterized by CD3+ neoplastic cells, as described in our study.…”
Section: Discussionsupporting
confidence: 62%
“…The most characteristic lesion common to all forms of canine cutaneous T cell lymphoma is the tropism of neoplastic cells in the epithelium (Fontaine et al, 2010). The classic neoplastic cells in canine cutaneous epitheliotropic lymphoma are CD3+ and CD20-cells (Martorell et al, 2011;Machado et al, 2015). More recently, Brachelente et al (2015) observed CD20+ CD3+ expression in CTCL, and this coexpression has been recognized in peripheral T-cell lymphomas.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations